A Case of Apparent Contact Dermatitis Caused by Toxocara Infection - Rosanna Qualizza; Eleni Makrì; Laura Losappio; Cristoforo Incorvaia (Case Reports in Dermatological Medicine)
Infection from Toxocara species may give rise to a large array of clinical symptoms, including apparent manifestations of allergy such as asthma, urticaria/angioedema, and dermatitis. We report a case, thus far not described, of contact dermatitis attributed to nickel allergy but caused by Toxocara infection. The patient was a 53-year-old woman presenting from 10 years a dermatitis affecting head, neck, and thorax. Patch tests initially performed gave a positive result to nickel, but avoidance of contact with nickel did not result in recovery. The patient referred to our Allergy Service in 2010 because of dermatitis to feet. Patch testing confirmed the positive result for nickel, but expanding the investigation a positive result for IgG antibodies to Toxocara was detected by Western blotting and ELISA. Treatment with mebendazole achieved immediate efficacy on feet dermatitis. Then, two courses of treatment with albendazole resulted in complete regression of dermatitis accompanied by development of negative ELISA and Western blotting for Toxocara antibodies. This report adds another misleading presentation of Toxocara infection as apparent contact dermatitis caused by nickel and suggests bearing in mind, in cases of contact dermatitis not responding to avoidance of the responsible hapten and to medical treatment, the possible causative role of Toxocara.